Hypertriglyceridemia with acute pancreatitis in a 14-year-old girl with diabetic ketoacidosis - Hyojung Park; Min-Sun Kim; Jiyeon Kim; Sae-Mi Lee; Sung Yoon Cho; Eun-Gyong Yoo; Dong-Kyu Jin (Korean Society of Pediatric Endocrinology, 2022)
Diabetic ketoacidosis (DKA) is a medically fatal condition in poorly controlled hyperglycemia or newly diagnosed diabetes mellitus. Severe hypertriglyceridemia (HTG) is an uncommon complication of DKA and can be associated with acute pancreatitis (AP). We present the clinical manifestations, laboratory findings, and management of AP associated with HTG in a 14-year-old girl with DKA. The patient, with a 7-year history of type 2 diabetes presented with epigastric pain, 1 month after stopping insulin injection. DKA, severe HTG, and AP were diagnosed based on the laboratory and imaging tests. She recovered from DKA after conventional treatment for DKA, and her triglyceride (TG) level was reduced from 10,867 mg/dL to the normal range after 7 days of admission without antilipid medication. Given that her C-peptide level was not too low and considering her negative diabetes-related antibodies and high TG level, targeted gene panel sequencing was performed on the genes associated with diabetes and HTG. We identified a heterozygous mutation, c.4607C>T (p. Ala1537Val), in ABCC8 related to maturityonset diabetes of the young (MODY) 12. To our knowledge, this is the first reported case of HTG-induced AP with DKA in a patient with MODY. In addition, we reviewed the literature for pediatric cases of HTG with DKA. In patients with DKA, timely awareness of severe HTG related to insulin deficiency is crucial for improving the consequences of AP. We recommend considering AP in all DKA patients presenting with severe HTG to ensure early and proper management.